GLOMERULAR HYPERFILTRATION AS AN EARLY MARKER OF RENAL DYSFUNCTION IN MASKED HYPERTENSION. (June 2018) - Sheng, C.S.; Zhang, D.Y.; Guo, Q.H.; Cheng, Y.B.; Huang, Q.F.; Wang, Y.; Wang, J.G.; Li, Y.
Abstract : Objective: Glomerular hyperfiltration, an early marker of renal dysfunction, is prevalent in the early stage of hypertension but had not been investigated in masked hypertension. The aim of the present study is to investigate the association of hyperfiltration with masked hypertension. Design and method: We recruited consecutive untreated outpatients who were referred for 24-h ambulatory blood pressure monitoring to the Hypertension Clinic. Masked hypertension was defined as an elevated 24-hour ambulatory blood pressure (> = 130/80 mm Hg) with a normal office blood pressure (<140/90 mm Hg). Glomerular hyperfiltration was defined as estimated glomerular filtration rate (eGFR) above the sex-and age- specific 95th percentile of normotensive subjects. Results: Among the 1768 participants (mean age, 50.9 years; 52.9% women), 646 (36.5%) had masked hypertension, 88 (5.0%) had microalbuminuria, and 176 (10.0%) had glomerular hyperfiltration. In multivariate analyses, glomerular hyperfiltration was independently associated with younger age, female sex, increased body mass index, 24-h systolic blood pressure and heart rate, and the presence of diabetes mellitus. The prevalence of glomerular hyperfiltration was significantly higher in masked hypertension compared with that in normotensives (12.2% vs.5.1%, P < 0.001), with an adjusted odds ratio of 2.42 (95% CI: 1.20–4.89, P = 0.01). The corresponding difference in prevalence (12.4% vs. 5.2%, P < 0.001) and the adjusted odds ratio (2.33, 95%CI, 1.44–3.76, P = 0.005) remained significant after excluding 88 patients with microalbuminuria. Conclusions: In conclusion, glomerular hyperfiltration was prevalent in masked hypertension as an early marker of renal damage.